Ligand-, copper-, and amine-free one-pot synthesis of 2-substituted indoles via Sonogashira coupling 5-endo-dig cyclization - Palimkar, Sanjay S.; Kumar, P. Harish; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron, 2006)
Results of the optimized conditions for the one-pot synthesis of 2-substituted indoles via palladium acetate catalyzed tandem Sonogashira coupling 5-endo-dig cyclization at room temperature under ultrasonic irradiation and standard stirred conditions are described. Electron-donating and electron-withdrawing groups present in both Coupling partners were well tolerated under these mild conditions. A copper-, ligand- and amine-free condition is an important feature of this protocol. Significant enhancement of reaction rates was observed for the reactions employing ultrasonic irradiation. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 5-endo-dig cyclization; Indole; synthesis; Ultrasound

Efficient synthesis of 1,8-dioxo-octahydro-xanthene derivatives promoted by a room temperature ionic liquid at ambient conditions under ultrasound irradiation - Venkatesan, K.; Pujari, Suresh S.; Lahoti, Rajgopal J.; Srinivasan, K. V. (Ultrasonics Sonochemistry, 2008)
The condensation reaction involving an aldehyde and diketone was efficiently promoted by the Ionic liquid, [Hbim]BF(4) (IL) as a reaction medium with methanol as co-solvent at ambient temperature under ultrasonic irradiation to afford the corresponding 1,8-dioxo-octahydroxantliene (xanthene) derivatives in excellent yields. The advantages of this method include among others the use of a recyclable, non-volatile ionic liquid, which promotes this protocol under ambient temperature without the requirement of ally added catalyst. The reaction times and yields are compared with p-TSA catalyzed synthesis of xanthenes under thermal conditions, which is also reported for the first time under our reaction conditions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: aldehydes; ambient conditions; Bronsted acidity; dimedone; Ionic liquid; Ultrasound; Xanthenes